2021
DOI: 10.3390/foods10112671
|View full text |Cite
|
Sign up to set email alerts
|

The Bactericidal Efficacy and the Mechanism of Action of Slightly Acidic Electrolyzed Water on Listeria monocytogenes’ Survival

Abstract: In the present work, the bactericidal efficacy and mechanism of slightly acidic electrolyzed water (SAEW) on L. monocytogenes were evaluated. The results showed that the strains of L. monocytogenes were killed completely within 30 s by SAEW whose available chlorine concentration (ACC) was higher than 12 mg/L, and it was confirmed that ACC is the main factor affecting the disinfection efficacy of SAEW. Moreover, our results demonstrated that SAEW could destroy the cell membrane of L. monocytogenes, which was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Similarly, chlorine solution has been found to induce the VBNC state in L. monocytogenes and Salmonella enterica at ACCs of 12 and 3 mg/L, respectively [ 17 ]. L. monocytogenes , in particular, was found to be completely eliminated using SAEW at an ACC of 12 mg/L [ 18 ]. Our findings, involving ACCs of 8–10 mg/L, are consistent with these observations ( Table 1 and Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, chlorine solution has been found to induce the VBNC state in L. monocytogenes and Salmonella enterica at ACCs of 12 and 3 mg/L, respectively [ 17 ]. L. monocytogenes , in particular, was found to be completely eliminated using SAEW at an ACC of 12 mg/L [ 18 ]. Our findings, involving ACCs of 8–10 mg/L, are consistent with these observations ( Table 1 and Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in these results might arise due to varying types of electrolyzed water used and the ratio of bacteria to SAEW. For instance, a previous study employed a bacteria-to-SAEW ratio of 1:9 [ 18 ], while our research utilized a 2:3 ratio. Despite these findings, studies exploring VBNC formation in Gram-positive bacteria induced by SAEW are relatively sparse.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the activities of SOD and CAT of Saprolegnia mycelium treated with different dilutions of AEW were examined, and it was found that both enzyme activities of Saprolegnia mycelium were signi cantly reduced in different treatment groups compared to the control group. Similarly, Li et al (Li Liang et al 2021a) investigated the effect of AEW on SOD, CAT and GSH-PX (glutathione peroxidase) activities in Listeria monocytogenes and found that AEW had no signi cant effect on SOD enzyme activity but signi cantly reduced CAT and GSH-PX activities. The results of this experiment were not consistent with the results of the present study, probably because Listeria monocytogenes and Saprolegnia are not the same type of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…SAEW was prepared using an Electrolyzed Water Generation device (Harmony-Ⅱ, Ruiande environmental equipment Company Ltd., Beijng, China). The electrolytic current was set as 19.2 A. Distilled water was used to prepare 50 mL electrolyte solution composed of 10% NaCl and 1% HCl solutions [ 14 ]. The electrolyte solution and 4 L distilled water were pumped into SAEW generator together and electrolyzed for 8.5 min to obtain SAEW.…”
Section: Methodsmentioning
confidence: 99%